A New Screening Questionnaire to Identify Patients With Dry Eye With a High Likelihood of Having Sjögren Syndrome. Issue 2 (February 2021) - Bunya, Vatinee Y.; Maguire, Maureen G.; Akpek, Esen K.; Massaro-Giordano, Mina; Hennessy, Sean; Vivino, Frederick B.; Gonzales, John A.; Baer, Alan N.; Ying, Gui-Shuang
Abstract : Purpose: To develop a screening questionnaire to identify patients with dry eye with a high likelihood of having underlying Sjögren syndrome (SS). Methods: This was a cross-sectional study of participants with dry eye complaints who were self-referred or referred by an ophthalmologist to the Sjögren's International Collaborative Clinical Alliance study. Symptoms and ocular surface examination findings were candidate predictors. Univariable and multivariable logistic regression analyses were performed to estimate odds ratios (ORs) and 95% confidence intervals (95% CI) for the association of a symptom and/or ocular sign with SS. Area under the receiver operating characteristic curve (AUC) was used to summarize the predictive ability of different regression models and the derived likelihood score. Results: Four questions were statistically significant in the final multivariable model: 1) Is your mouth dry when eating a meal? [Yes = OR 1.63 (1.18–2.26)]; 2) Can you eat a cracker without drinking a fluid or liquid? [No = OR 1.46 (1.06–2.01)]; 3) How often do you have excessive tearing? [None of the time = OR 4.06 (1.81–9.10)]; and 4) Are you able to produce tears? [No = OR 2.24 (1.62–3.09)]. The SS likelihood score had an AUC of 0.70 (95% CI, 0.66–0.73), and when including tear break-up time and conjunctival staining, it yielded an AUC of 0.79 (95% CI, 0.77–0.82). Conclusions: This questionnaire can be used to identify patients with dry eye with a high likelihood of having SS. With future refinement and validation, this screening tool could be used alone or in combination with examination findings to identify patients with SS earlier, thereby facilitating better clinical outcomes. Abstract : Supplemental Digital Content is Available in the Text.